2006
DOI: 10.1039/b601096b
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of furanocoumarin monomers as inhibitors of CYP3A4

Abstract: A number of furanocoumarins isolated from grapefruit juice have been found to inhibit CYP3A4 activity in vitro. In this study, we have designed and synthesised a range of analogues based on bergamottin to investigate the relationship between chemical structure and inhibition of CYP3A4 activity. Studies were performed using human liver microsomes and human intestinal S9 fraction, with testosterone as the marker substrate. With the exception of the coumarin and phenolic furanocoumarin derivatives, which were ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 17 publications
(56 reference statements)
4
36
0
Order By: Relevance
“…The synthesis of AUR was based on a literature procedure [10], modified as follows. Geranyl chloride (42 g, 0.24 mol), synthesized as reported elsewhere [11], was added to a 2-L round bottom flask along with acetone (800 mL), potassium carbonate (45 g, 0.32 mol), and 7-hydroxycoumarin (35.8 g, 0.22 mol), obtained from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of AUR was based on a literature procedure [10], modified as follows. Geranyl chloride (42 g, 0.24 mol), synthesized as reported elsewhere [11], was added to a 2-L round bottom flask along with acetone (800 mL), potassium carbonate (45 g, 0.32 mol), and 7-hydroxycoumarin (35.8 g, 0.22 mol), obtained from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…We consider that Cou and (or) VO should enhance the analgesic effect of CA is related to the improvement of plasma concentration of dl-THP. 4-and 9-Prenyl furo(3,2-g)benzopyran-7-ones, closely related to furocoumarins of grapefruit juice involved in the modification in the pharmacokinetics of various active principles, through modulation of their metabolism by hepatic cytochrome P450 (Guo et al, 2000;Bellevue et al, 1997;Row et al, 2006). 4-and 9-Prenyl furo(3,2-g)benzopyran-7-ones are also major coumarins of Angelica dahurica, and Cou are involved in the modification in the pharmacokinetics of dl-THP in CA that may be related to these components.…”
Section: Discussionmentioning
confidence: 99%
“…15) On the other hand, BT did not inhibit CYP3A activities in microsomes from humans and rats. 5,16) Furthermore, the uptake experiment of vinblastine by Caco-2 cells revealed that BT has little inhibitory effect on P-glycoprotein unlike BG and DHB.…”
Section: Discussionmentioning
confidence: 99%